Histocytopathological Types of Lung Carcinoma and Its Correlation with Various Pathological Parameters - Dhakal, B.; Makaju, R.; Shrestha, B. (Devdaha Medical Journal, 2024)
Introduction: Lung cancer in Nepal is the most common cancer in men (18% of new cases diagnosed) and the third most common cancer in women (7.7%). Nine percent of total annual deaths are due to cancer. Carcinoma of lung is classified histologically into small-cell lung carcinoma (SCLC) and non-small-cell lung carcinoma (NSCLC). The objective of this study is to find histopathological types of lung carcinoma in adult Nepalese population and to find correlation of lung carcinoma with age, sex, smoking-behavior and SCLC versus NSCLC. Methods: Age, sex and various histological parameters were noted in cases of lung specimens at Dhulikhel, Kathmandu University Hospital. Other clinical parameters were traced back. The reports were analyzed with cytology, Biopsy and Immunohistochemistry (IHC) in four cases. Results: Among 122 cases, 74 were the specimens of biopsy and 48 of FNAC. Fifty-four of them were positive for malignancy with specific subcategorization of tumors. Among them 30 (55.5 %) were Squamous cell carcinoma (SCC), 8 (14.8%) were Adenocarcinoma, one (1.8%) adenosquamous carcinoma, nine (16.6%) NSCLC Not Otherwise Specified (NOS) and six (11.1%) were Small cell carcinoma. Mean age of the patients was 63.1 years, male to female ratio 1.5:1 and 79.6% of the patients having lung cancer were smokers. Conclusion: SCC was found to be the most common subtype, instead of globally reported incidence of adenocarcinoma. Most cases are above 50 years old and have history of smoking.